Формування соціальних витрат підприємств у процесі реалізації соціального захисту працівників - Фоменко, Г.Г. (Економіка промисловості, 2012)
Досліджено причини участі суб’єктів господарювання у соціальному захисті працівників; визначено поняття «соціальний захист», «соціальний захист працівників» та «соціальні витрати підприємства»; висвітлено процес формування соціальних витрат підприємств у процесі реалізації соціального захисту працівників.
Ключові слова: соціальний захист, соціальний захист працівників, соціальні витрати, соціальна відповідальність бізнесу, соціальна політика. Исследованы причины участия субъектов хозяйствования в социальной защите работников, определены понятия «социальная защита», «социальная защита работников» и «социальные расходы предприятия», представлен процесс формирования социальных расходов предприятий в процессе реализации социальной защиты работников.
Ключевые слова: социальная защита, социальная защита работников, социальные расходы, социальная ответственность бизнеса, социальная политика. We study the formation of social costs of the enterprise in the implementation of social protection. Social protection of workers is a necessary condition for the functioning of each independent socially-oriented state. Employers bear the greatest responsibility for the implementation of social protection. This is accompanied by the emergence of problems associated with the formation of an effective management system in the area of human resources. The actual problems in the context of social protection are issues of formation of social costs, management and cost control at the enterprise level.
The aim of the article is to study the composition of economic actors, methods and areas of social protection as a basis for social expenditures. The object of the study is the formation of social costs at the enterprise. The subject of the article is social protection of workers at the enterprise. The author uses such methods as system analysis, heuristic methods, and methods of induction and deduction.
Social protection of employees is the essential function of each socially developed country. Every social institution is responsible for the implementation of social protection depending on the chosen social policy. There are three main reasons for entities participating in social security. The first one is legally fixed nature of minimum social guarantees provided by the state, the second one is that to ensure social protection of workers at a decent level is a way to motivate employees, and the third oneis the necessity of socially responsible business, which is a necessity in the face of fierce competition in which social protection isa main component. As a result of social protection, participation in social partnership and the business social responsibility social costs are generated. They aim at providing statutory social minimum, additional social labor guarantees, social and cultural human development and socio-economic development of society. Proper accounting, control and management of such costs can significantly improve the performance of anenterprise and enhance its reputation in domestic and foreign markets.
Keywords: social protection, social protection of workers, social costs, social responsibility, social policy.